Bone mineral density in women using the subdermal contraceptive implant Implanon for at least 2 years - Pongsatha S. (2014)
Objective: To compare the effect of the long-term use of a subdermal single-rod contraceptive implant on bone mineral density (BMD) between users and a control group. Methods: In this cross-sectional study, BMD was measured at the lumbar spine, femur, and distal radius and ulna in 100 Thai women of reproductive age, 50 who had used the Implanon implant for contraception for at least 2 years and 50 controls. Results: Ethnicity, age, age at menarche, parity, menstrual pattern, and body mass index were similar in the 2 groups. The mean duration of Implanon use was 32.8 ± 6.3 months. Although the prevalence of osteoporosis was rare at all sites in both groups, the Implanon users had a significantly lower BMD at the distal radius and ulna than the controls. Conclusion: The long-term use of Implanon seemed to have a negative impact on the mineral density of the distal radius and ulna. © 2010 International Federation of Gynecology and Obstetrics.